Annual dormancy cycles in buried seeds of shrub species: germination ecology of Sideritis serrata (Labiatae). (28th January 2015) - Copete, M. A.; Herranz, J. M.; Ferrandis, P.; Copete, E.; Bekker, R.
Abstract The germination ecology of Sideritis serrata was investigated in order to improve ex‐situ propagation techniques and management of their habitat. Specifically, we analysed: (i) influence of temperature, light conditions and seed age on germination patterns; (ii) phenology of germination; (iii) germinative response of buried seeds to seasonal temperature changes; (iv) temperature requirements for induction and breaking of secondary dormancy; (v) ability to form persistent soil seed banks; and (vi) seed bank dynamics. Freshly matured seeds showed conditional physiological dormancy, germinating at low and cool temperatures but not at high ones (28/14 and 32/18 °C). Germination ability increased with time of dry storage, suggesting the existence of non‐deep physiological dormancy. Under unheated shade‐house conditions, germination was concentrated in the first autumn. S. serrata seeds buried and exposed to natural seasonal temperature variations in the shade‐house, exhibited an annual conditional dormancy/non‐dormancy cycle, coming out of conditional dormancy in summer and re‐entering it in winter. Non‐dormant seeds were clearly induced into dormancy when stratified at 5 or 15/4 °C for 8 weeks. Dormant seeds, stratified at 28/14 or 32/18 °C for 16 weeks, became non‐dormant if they were subsequently incubated over a temperature range from 15/4 to 32/18 °C. S. serrata is able to form small persistent soil seed banks. The maximum seed life span in the soil was 4 years, decreasing with burial depth. This is the second report of an annual conditional dormancy/non‐dormancy cycle in seeds of shrub species.